An exploration of prospective imagery: the impact of future events scale. - Deeprose, C; Holmes, E (2010)
BACKGROUND: Mental imagery of the future has clear clinical importance, although little is known about intrusive, prospective imagery of personally-relevant events. Currently, no measure is available to assess this. AIMS: The Impact of Future Events Scale (IFES) was created to assess the impact of intrusive, prospective, personally-relevant imagery. It was examined in relation to predictions about dysphoria. METHOD: To form the IFES, the IES-R (a measure of the impact of a past traumatic event on posttraumatic stress disorder symptomatology such as intrusive re-experiencing) was adapted item-by-item to assess intrusive "pre-experiencing" and imagery of specific, future events. Participants (N = 75) completed the IFES and assessments of depression, anxiety and general imagery use. RESULTS: As predicted, the IFES significantly and positively correlated with depression scores. Analyses using subgroups of non-dysphoric and mild-dysphoric participants confirmed that the mild-dysphoric group reported significantly higher IFES scores, indicating higher levels of pre-experiencing of the future and related hyperarousal and avoidance. CONCLUSIONS: IFES provides a measure of the impact of "pre-experiencing" in the form of intrusive prospective, personally-relevant imagery, with sensitivity to group differences on the basis of depression scores. Further research is required to extend these finding into clinical depression and other psychopathological conditions.